2021
DOI: 10.1177/09610006211014277
|View full text |Cite
|
Sign up to set email alerts
|

Correlatives of business students’ perceived information literacy self-efficacy in the digital information environment

Abstract: Self-efficacy toward information literacy is and has been demonstrated as an essential and fundamental key for academic performance and lifelong learning of students at all levels. This research reported the results of a cross-sectional survey carried out to investigate the correlatives of information literacy self-efficacy among business students at the University of Management and Technology, Lahore. The questionnaire contained an Information Literacy Self-Efficacy Scale, which along with sociodemographic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
(90 reference statements)
2
11
0
Order By: Relevance
“…A closer look at the analysis discovered that the lawyers who participated in the survey felt more competent in basic IL skills such as understanding of different legal systems, task conceptualization, defining precisely legal information needs, identifying potential information sources, gathering information from multiple sources, determining the information quality, understanding the laws governing the lawyers’ information use, comprehending and applying legal research skill. These findings were expected as academic libraries in Pakistan did not impart advanced levels of IL in Pakistan (Anwar and Naveed, 2019; Naveed, 2022; Naveed and Mahmood, 2019, 2021). These findings needed to be interpreted considering the theory of the Dunning-Kruger effect as low performers overstate their IL skills in most of the cases (Mahmood, 2016).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A closer look at the analysis discovered that the lawyers who participated in the survey felt more competent in basic IL skills such as understanding of different legal systems, task conceptualization, defining precisely legal information needs, identifying potential information sources, gathering information from multiple sources, determining the information quality, understanding the laws governing the lawyers’ information use, comprehending and applying legal research skill. These findings were expected as academic libraries in Pakistan did not impart advanced levels of IL in Pakistan (Anwar and Naveed, 2019; Naveed, 2022; Naveed and Mahmood, 2019, 2021). These findings needed to be interpreted considering the theory of the Dunning-Kruger effect as low performers overstate their IL skills in most of the cases (Mahmood, 2016).…”
Section: Discussionmentioning
confidence: 81%
“…This finding was anticipated and not surprising as special libraries did not make such provisions to impart IL instruction in Pakistan (Anwar and Naveed, 2019; Naveed, 2022; Naveed and Rafique, 2018). The IL instruction programs being offered in most of the academic libraries were in the embryonic stage and far behind those of the developed world (Anwar and Naveed, 2019; Hamid and Ahmad, 2016; Kousar and Mahmood, 2015; Naveed, 2022; Naveed and Mahmood, 2019, 2021; Naveed and Rafique, 2018; Ullah and Ameen, 2014). This result corroborated the results of Naveed (2022), and Naveed and Rafique (2018) who also reported similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…Similar research conducted by James et al (2019) exposed that the majority of students lacked advanced search strategies and faced trouble in rating and accessing the information resources. Conversely, Naveed and Mahmood (2021) perceived students' low level self‐efficacy not only in searching but in defining information needs, accessing resources, evaluating sources, interpreting, synthesising and ethically using information, and finally communicating the information through the proper channel.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers suggested that the use of plagiarism checkers has failed to stop the practice just as academic codes of conduct by the postgraduate researchers and lecturers have not worked (Amunga, 2013). It was strongly recommended that university administration should introduce ethics courses as university prerequisite courses apart from the compulsory core courses (Arefeen et al, 2020; Brown, 1999; Carbo, 2005; Carbo & Almagno, 2001; Dadzie, 2011; Maughan, 2001; Naveed & Mahmood, 2021; Nero, 1999). So, behaviour change should be brought about by a deep understanding of IL and IE and the need to embrace positive practices in regard to access and use of information in university and life‐long practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CILIP [ 7 ] defined information literacy as ‘the ability to think critically and make balanced judgments about any information we find and use. It empowers us as citizens to develop informed views and to engage fully with society.’ Information literacy plays an important role in the capacity building of students to undertake information related tasks, make the best use of information and adopt appropriate information behaviour to achieve educational and career goals [ 8 ]. It also influences positively students’ academic engagement and academic performance [ 9–11 ].…”
Section: Introductionmentioning
confidence: 99%